Integrating Primary School Teacher Education Students' TPACK Competence in Developing C6-Level HOTS Questions - Mintohari, Mintohari; Suryanti, Suryanti; Suprayitno, Suprayitno; Julianto, Julianto; Wiryanto, Wiryanto; Yoka Putri, Arizkylia (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2025)
Objective: This study aims to analyze the ability of students in the Primary School Teacher Education program to integrate Technological Pedagogical Content Knowledge (TPACK) in developing mathematics questions based on Higher-Order Thinking Skills (HOTS) at the C6 level (creating). This competence is essential for preparing future teachers to design questions that foster creativity, problem-solving, and innovation among primary school students. Method: This research employed a qualitative descriptive approach involving final-semester students who had completed courses on instructional design and TPACK. Data were collected through documentation of C6-level HOTS question development assignments, semi-structured interviews, and classroom observations. Data were analyzed through data reduction, display, and conclusion drawing. Results: The findings indicate that most students demonstrated the ability to integrate TPACK components—content, pedagogy, and technology—in designing HOTS-based mathematics questions at the C6 level. While some questions reflected strong alignment with C6 indicators such as originality and contextual relevance, challenges remain in harmonizing all TPACK dimensions consistently. Variability in technological integration and depth of creativity was also observed. Novelty: This study offers insight into how TPACK competencies support the development of C6-level HOTS questions within primary mathematics education. It contributes to existing literature by linking TPACK directly with cognitive assessment design in teacher education and highlighting the preparedness of pre-service teachers to meet the demands of 21st-century learning.